Adaptive distributed auction-based algorithm for optimal mileage based AGC dispatch with high participation of renewable energy. (January 2021) - Zhang, Xiaoshun; Tan, Tian; Zhou, Bin; Yu, Tao; Yang, Bo; Huang, Xiaoming
Highlights: A new optimal mileage based automatic generation control dispatch is formulated. An adaptive distributed auction-based algorithm is proposed to handle AGC dispatch. The proposed method can be used in a performance-based frequency regulation market. The optimal mileage based AGC dispatch can be addressed in a distributed manner. The dynamic response performance of the control area can be dramatically improved. Abstract: In a performance-based frequency regulation market, increasing number of controllable renewable energy will actively participate in automatic generation control (AGC) of interconnected power girds. Under such circumstance, this paper develops a new optimal mileage based AGC dispatch (OMD) to optimally distribute the real-time overall AGC dispatch command among different AGC units, including traditional units (e.g., coal-fired unit) and renewable energy (e.g., wind farm). It aims to minimize the power deviation between the dispatch command and the actual power regulation output. To rapidly find a high-quality dispatch scheme in a distributed manner, a novel adaptive distributed auction-based algorithm (ADAA) is used for handling OMD due to its fast convergence speed and model-free feature. Compared with the original auction-based algorithm (AA) with multiple fixed swap sizes, ADAA can converge faster and reduce communication traffic since it only employs an adaptive swap size according to the immediate optimization results. Finally, an extended two-area load frequency control model and a practical Hainan power grid of southern China are employed to evaluate the performance of ADAA for OMD.